Serum enzymes markers in myocardial infarction: A study of rural area - Pochhi, Mamata; Muddeshwar, MG (Asian Journal of Medical Sciences, 2017)
Background: Acute Myocardial Infarction is the reduction of coronary flow to such an extent that supply of oxygen to the myocardium do not need the oxygen demand of myocardial tissues. The diagnosis of AMI cannot be fulfilled unless the elevated levels of serum cardiac enzymes particularly CK-MB iso-enzyme activity. The rate of release of cardiac enzymes is highly diagnostic. Aims and Objectives: Therefore, the present thesis aim is-in evaluating, whether the elevated levels of cardiac marker enzymes can be compared to the extent of the Myocardial infarction. Material and Methods: Therefore the present study was undertaken on 50 patients of MI and 50 patients of control. They were group according to the age and sex. The activity of different cardiac enzymes were studied. Result: The AMI patients had significantly elevated levels of 90% patients of high LDH values and 86% patients have elevated levels of AST. The significant elevation of serum enzymes as compared to the control. Conclusion: The magnitude of the elevated levels of enzymes can be compared to the extent of the myocardial infarction. Serum GGT can also be useful marker of oxidative stress in myocardial infarction. Asian Journal of Medical Sciences Vol.8(2) 2017 34-37